139k views
0 votes
Given f(x)=(2x-3)(3x+7), what is the y-intercept

User Kabarga
by
5.2k points

2 Answers

2 votes

Answer:

(0,-21)

Explanation:

The x value of a y intercept is always 0

So we can plug in 0 to the equation to solve for the y intercept

(2*0-3)(3*0+7)

-3*7= -21

y intercept: (0,-21)

User Demian Kasier
by
6.0k points
3 votes

Answer:

-21

Explanation:

f(x)=(2x-3)(3x+7)

The y intercept is when x=0

f(0) = (0-3) (0+7)

-3*7

-21

The y intercept is -21

User Eemz
by
5.6k points